Fungal Endophthalmitis in a Case of Rhino-Orbito-Cerebral Mucormycosis: Successfully Treated With Amphotericin B Colloidal Dispersion - Zhao, Yinlong; Tian, Wenbin; Yang, Jiankai; Li, Xueqing; Lu, Huaihai; Yu, Ning; Zhang, Pei; Liu, Chao; Chen, Pengfei; Lei, Guang; Liu, Ya (Frontiers in Microbiology, 2022)
Background: Rhino-orbito-cerebral mucormycosis (ROCM) is an acute, fulminant, opportunistic fungal infection that usually occurs in diabetes or immunocompromised patients. Amphotericin B combined with surgical debridement remains the standard treatment, although it is controversial due to its lager nephrotoxicity. Thus far, no studies have reported the treatment for ROCM associated fungal endophthalmitis because the exact pathogenesis and transmission routes in ROCM remain unclear. Here, we reported a case of ROCM complicated with fungal endophthalmitis treated favorably with amphotericin B colloidal dispersion (ABCD) in combination with other antifungals and surgical debridement. Case Presentation: A 34-year-old woman with diabetes was admitted to our hospital owing to right-sided headache for 8 days, blindness with swelling in the right eye for 5 days, and blindness in the left eye for 1 day. Magnetic resonance imaging showed that the patient had sphenoid sinus, sinuses, frontal lobe lesions and proptosis of the right eye. Metagenomic sequencing revealed that the patient had Rhizopus oryzae infection. During hospitalization, the patient received intravenous ABCD, oral posaconazole, and topical amphotericin B and underwent surgical debridement. After 67 days of treatment, the patient's condition was significantly improved, and limb muscle strength showed grade V. Rhizopus oryzae showed negative results, and conjunctival swelling decreased. Additionally, no nephrotoxicity occurred during treatment. After discharge, the patient’s treatment was transitioned to oral posaconazole and she was free of complaints during the 30-day follow-up without any additional treatment for ROCM. Discussion: Treatment with ABCD combined with other antifungal drugs and surgical debridement for ROCM complicated with fungal endophthalmitis showed remarkable efficacy and good safety. Hence, this regimen is a promising treatment strategy for this fatal disease.